Choosing a medical specialty course in Italy: explorative analysis of factors related to the choice - Paolo Trerotoli; Massimo Minerva; Nicola Bartolomeo; Massimo Giotta; Ilaria Dargenio; Giammaria Liuzzi; Carlo Signorelli (Epidemiology, Biostatistics and Public Health)
Background: In order to be able to access a course of medical or surgical specialization, in addition to the degree and the qualification to the profession it is necessary to perform an entrance test. In this study we wanted to analyze the possible factors that determined the choice of a given graduate school and the place where to attend it in the year 2021. Study design: Cross-sectional study to evaluate the association between the type of graduate school, the score class obtained at the admission test, the location of the graduate school and the location of the degree. Methods: The evaluation of the association between site of specialty admission and degree, score at degree and score at admission test was performed by multiple correspondences analysis (MCA). Then, through a logistic regression model, the Odds Ratios (OR) and the respective confidence interval with 95% (95%CI) confidence level of the covariates on the probability of remaining in the same degree site, or in the same region or in the same geographical area, were estimated. Results The highest admission score and the highest age are significantly and independently associated with the probability of choosing, as a graduate school location, the same location where the degree was obtained. Conclusion: In conclusion, the choice of the course and the location of the specialty course is made in most cases, taking into account the score made in the exam, based on the location where you attended the course of study in medicine and surgery.